IEEE Access Special Section Editorial: Recent Developments in Consensus Problems for Complex Networked Systems - Yilun Shang; Dequan Li; Zhaoxia Peng; Ali Heydari; Kamran Turkoglu; Johan Thunberg (IEEE Access, 2018)
Consensus problems for complex networked systems composed of interconnected interacting agents have received considerable attention in recent years partly due to the ever-increasing number of applications in various areas, such as swarm dynamics, smart grids, sensor networks, intelligent transportation systems, unmanned aerial vehicles, telerobotics, and the military. The design of consensus protocols takes advantage of nearest neighbor interaction rules, which renders a framework of distributed multi-agent systems so that the group of dynamic agents can reach an agreement or consensus on certain desired cooperative tasks. The growing complexity of the communication topology and agents’ dynamics along with the great demands on system performance brings numerous challenges including consensus under switching topologies, interdependent networks, time-varying transmission delays, parameter variations, uncertainties, nonlinearities, etc. Moreover, deep links between network science and control theory have been gradually revealed within the last couple of years, which shed light into the consensus problem and make it a rather promising direction.